The Bioavailability of Glycyrrhizinic Acid Was Enhanced by Probiotic Lactobacillus rhamnosus R0011 Supplementation in Liver Fibrosis Rats - Li, Huifang; Wang, Jing; Fu, Yifan; Zhu, Ke; Dong, Zhiling; Shan, Jinjun; Di, Liuqing; Jiang, Shu; Yuan, Tianjie (Nutrients, 2022)
Glycyrrhizinic acid (GL) is clinically applied to treat liver injury, and the bioavailability of orally administered GL is closely related to the gut microbiota. Therefore, the dysbiosis of gut flora in liver injury could significantly influence GL bioavailability. Still, less is known about the impact of probiotic supplementation on the bio-absorption process of oral medication, especially under a pathological state. Herein, probiotic L. rhamnosus R0011 (R0011) with a high viability in the harsh gastrointestinal environment was selected, and the effect of R0011 on the GL bioavailability in rats was investigated. Four groups of rats (n = 6 per group) were included: the normal group (N group), the normal group supplemented with R0011 (NLGG group), CCl4-induced chronic liver injury model (M group), and the model group supplemented with R0011 (MLGG group). Our results showed that liver injury was successfully induced in the M and MLGG groups via an intraperitoneal injection of 50% (v/v) CCl4 solution. Healthy rats supplemented with R0011 could increase the bioavailability of GL by 1.4-fold compared with the normal group by plasma pharmacokinetic analysis. Moreover, the GL bioavailability of MLGG group was significantly increased by 4.5-fold compared with the model group. R0011 directly improved gut microbial glucuronidase and downregulated the host intestinal drug transporter gene expression of multidrug resistance protein 2 (MRP2). More critically, R0011 restored the gut microbiota composition and regulated the metabolic function, significantly enhancing the microbial tryptophan metabolic pathway compared with the pathological state, which may indirectly promote the bioavailability of GL. Overall, these data may provide possible strategies by which to address the low bioavailability of traditional medicine through probiotic intervention.